Assessment of Some Hematological parameters in Iraqi Women with Different Breast Cancer Stages - M. Ali, Zahra; H. Ali, Shatha; Y. Mohsen, Forat (Iraqi Journal of Pharmaceutical Sciences, 2020)
Breast cancer (BC) is the most commonly diagnosed cancer in women. The metabolism of iron is closely regulated by hepcidin which exerts its action by interacting with a ferroportin. The aim of the present study was to assess the alterations in the levels of some serum biomarkers that have a role in iron homeostasis (hepcidin and ferroportin) in addition to hematological parameters (hemoglobin, leukocyte and platelets count) in different stages of BC. This study included 66 women with BC. The patients were categorized as follows : group 1 includes :22 patients with stage I disease ,group 2 includes: 22 patients with stage II disease ,and group 3 include: 22 patients with stage III disease .Group 4 includes :22 apparently healthy women as control. Data analysis revealed a significant elevation of serum hepcidin levels of patients groups 1, 2, and 3 (437.2±26.4, 501.4±31.8 and 558.5±21.3 pg/ml respectively) ,vs (179.4±19.8 pg/ml) of control, with steady elevations from stage I to III . Furthermore, serum ferroportin levels were significantly lowered in groups 1 and 3 compared to control (0.589±0.107 and 0.733±0.1 vs 1.37±0.28 ng/ml respectively).While blood hemoglobin level of group 3 were lower (11.96±0.18 vs 12.7±0.13g/dl ) compared with controls . Blood leukocyte count of patients (all groups) (7.39±0.28 ,8.93±0.48,9.86±0.52 (^103/µl) respectively) were markedly increased compared to controls (6.06±0.23), while mean platelet count for patients in group 2&3 were significantly increased compared to controls (313.9±19.3,309.2±25.3 vs 233.3±9.1 respectively). In conclusion, hepcidin, ferroportin and hematological markers including hemoglobin, WBC count and platelets count are altered in women with BC compared to healthy control. The changes occur mostly in accordance with disease stages.